Effectiveness of Montmorillonite-ZnO as Photocatalyst for Adsorption and Degradation of Methylene Blue - Abdillah Mushawwir An Nur; Ilma Kanzu Iklima; Taupik Hidayat; I Wayan Dasna; Sumari Sumari; Yudhi Utomo (Indonesian Journal of Chemical Research, 2026)
This study aims to synthesize, characterize, and evaluate the photocatalytic activity of a montmorillonite–ZnO (MMT/ZnO) composite for the degradation of methylene blue (MB) under ultraviolet (UV) and dark (non-UV) conditions. The composite was prepared by mixing synthetic montmorillonite derived from Indonesian soil with ZnO in ethanol, followed by calcination at 400 °C for 2 hours, and subsequently characterized using X-ray fluorescence (XRF). The degradation tests were performed using various composite masses (0.5–2.5 g) and compared with single ZnO and montmorillonite materials through visible spectrophotometry analysis. The results revealed that under UV irradiation, MMT/ZnO achieved the highest degradation efficiency of 98.37%, while under non-UV conditions, MB removal remained high at 88.39%, primarily driven by adsorption. These findings confirm a synergistic effect between the adsorption capacity of montmorillonite and the photocatalytic activity of ZnO, where adsorption dominated MB removal while photocatalysis contributed to enhancing overall degradation efficiency. The novelty of this study lies in the utilization of synthetic Indonesian montmorillonite as a ZnO support, which enhances photocatalytic efficiency while reducing production costs. This finding highlights the potential of MMT/ZnO composites as an environmentally friendly and cost-effective alternative for dye wastewater treatment in the textile industry.